Health workforce protection and preparedness during the COVID-19 pandemic: a tool for the rapid assessment of EU health systems. (9th November 2021) - Kuhlmann, Ellen; Brînzac, Monica-Georgiana; Burau, Viola; Correia, Tiago; Ungureanu, Marius-Ionut
Abstract: This article is dedicated to the WHO International Year of Health and Care Workers in 2021 in recognition of their commitment during the COVID-19 pandemic. The study aims to strengthen health workforce preparedness, protection and ultimately resilience during a pandemic. We argue for a health system approach and introduce a tool for rapid comparative assessment based on integrated multi-level governance. We draw on secondary sources and expert information, including material from Denmark, Germany, Portugal and Romania. The results reveal similar developments across countries: action has been taken to improve physical protection, digitalization and prioritization of healthcare worker vaccination, whereas social and mental health support programmes were weak or missing. Developments were more diverse in relation to occupational and organizational preparedness: some ad-hoc transformations of work routines and tasks were observed in all countries, yet skill-mix innovation and collaboration were strongest in Demark and weak in Portugal and Romania. Major governance gaps exist in relation to education and health integration, surveillance, social and mental health support programmes, gendered issues of health workforce capacity and integration of migrant healthcare workers (HCW). There is a need to step up efforts and make health systems more accountable to the needs of HCW during global public health emergencies.